2016
DOI: 10.1002/etc.3612
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of immune and antioxidant responses by azinphos‐methyl in the freshwater mussel Diplodon chilensis challenged with Escherichia coli

Abstract: The aim of the present study was to characterize the immune response-total hemocyte number, cell type proportion, hemocyte viability, lysosomal membrane stability, phagocytic activity, cellular acid and alkaline phosphatase activity, and humoral bacteriolytic and phenoloxidase activity--in Diplodon chilensis exposed to 0.2 mg/L of azinphos-methyl (AZM), using Escherichia coli as immunological and pro-oxidant challenges. In addition, glutathione-S-transferase and lipid peroxidation thiobarbituric acid reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 58 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…Moreover, Neškovic et al (1996) found an increase in ALP activity in the liver and heart of the fish Cyprinus carpio exposed to 5 and 10 mg L −1 of glyphosate acid. The increase in ALP activity of L. fortunei with dietary glyphosate exposure could be related with a modulation of the immune response and/or cellular damage, as has been postulated for the clams D. chilensis and A. rhombea exposed to pesticides (Castro et al, 2017;Ranilalitha et al, 2014)…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Moreover, Neškovic et al (1996) found an increase in ALP activity in the liver and heart of the fish Cyprinus carpio exposed to 5 and 10 mg L −1 of glyphosate acid. The increase in ALP activity of L. fortunei with dietary glyphosate exposure could be related with a modulation of the immune response and/or cellular damage, as has been postulated for the clams D. chilensis and A. rhombea exposed to pesticides (Castro et al, 2017;Ranilalitha et al, 2014)…”
Section: Discussionmentioning
confidence: 86%
“…Alterations in ALP activity have been associated with the response to contaminants exposure. For example, Castro et al (2017) recorded an induction of ALP activity in hemocytes of the clam Diplodon chilensis exposed to the pesticide azinphos-methyl, Aanand et al (2010) observed an induction of ALP activity in gut and adductor muscle in the mussel Perna viridis exposed to metals and Ranilalitha et al (2014) recorded an increase in ALP activity in the digestive gland of the clam Anadara rhombea exposed to pesticide tributyltin chloride. Moreover, Neškovic et al (1996) found an increase in ALP activity in the liver and heart of the fish Cyprinus carpio exposed to 5 and 10 mg L −1 of glyphosate acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemolymph (1 mL) was withdrawn from the adductor muscle of 6 individuals per time and site using a sterile syringe and working on ice. Part of the hemolymph was used for lysosomal membrane stability and the remaining was washed and resuspended in anticoagulant solution (3 g L −1 glucose and 0.36 g L −1 trisodium citrate, 60 mOsm L −1 , pH 7, Castro et al, 2017) to obtain the hemocytes fraction for measuring ROS production. Hemocytes lysosomal membrane stability was measured by the neutral red retention time (NRRT50) method (modified from Mamaca et al, 2005).…”
Section: Effects On Hemocytesmentioning
confidence: 99%
“…In freshwater species, like Diplodon chilensis, granulocytes have higher phagocytic activity, but hyalinocytes represent >90% of the total hemocytes. Thus, hyalinocytes are the principal immune response cells (Castro et al, 2017(Castro et al, , 2018. In addition, humoral soluble factors, such as antimicrobial peptides, lectins, lysosomal hydrolases, and phenol oxidase, are released by cells into the hemolymph and participate in processes of melanization/encapsulation and wound healing.…”
Section: Introductionmentioning
confidence: 99%